The Influence of Work Motivation and Workload on Work Fatigue among Mechanic at the Train Maintenance Centre in Yogyakarta - Diah Suci Rahmawati; Adi Heryadi (Indonesian Psychological Research, 2024)
The amount of risk and job demands, and monotony of work and task deadlines that are too short, can affect the decrease in employee work motivation. Work motivation can affect work fatigue through work capacity, workload and work stress. The purpose of this study was to determine the effect between work motivation and workload on work fatigue in employees of Maintenance Center Unit (UPT) Balai Yasa Yogyakarta in the production department. The research method used is quantitative research with a correlational approach. The sampling process is carried out using the purposive sampling method, with criteria for being 20 – 56 years old and having worked at UPT Balai Yasa Yogyakarta for at least 1 year. The instrument used to collect the data in this study were work fatigue scale, work motivation scale, and workload scale. The results of this study show that: work motivation has an influence on the condition of work fatigue of UPT Balai Yasa Yogyakarta employees, workload also has an influence on work fatigue of UPT Balai Yasa Yogyakarta employees, and motivation and workload have an influence together on the condition of work fatigue of UPT Balai Yasa Yogyakarta employees.